The Effectiveness of Leaflet Media Intervention on Improving Knowledge, Attitudes, Practices, and Compliance with Personal Protective Equipment Use Among Clinical Dental Students at a Dental Hospital - Natasya Indah S. Manalu; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (PROFESSIONAL HEALTH JOURNAL, 2026)
Background: Clinical clerkship (co-ass) students in dental hospitals are at high risk of occupational exposure to infectious diseases, yet compliance with personal protective equipment (PPE) remains low. This study aimed to evaluate the effect of a leaflet-based educational intervention on knowledge, attitudes, practices, and compliance regarding PPE use among clinical dental students. Methods: A quasi-experimental study with a one-group pre-test and post-test design was conducted at the Dental and Oral Hospital, Universitas Sumatera Utara, involving 150 clinical clerkship students selected through simple random sampling. A validated questionnaire was used to measure knowledge, attitudes, practices, and compliance before and after the leaflet intervention. Data were analyzed using the Wilcoxon signed-rank test (α = 0.05). Results: After the intervention, the proportion of respondents with good knowledge increased from 20.0% to 83.3%, good attitudes from 14.7% to 64.7%, good practices from 23.3% to 75.3%, and good compliance from 23.3% to 80.0%. Mean scores increased significantly for all variables: knowledge (2.42±1.23 to 6.33±2.36), attitudes (14.07±2.33 to 20.51±2.45), practices (11.27±1.84 to 17.11±1.77), and compliance (23.13±2.61 to 33.64±2.75). The Wilcoxon test yielded p = 0.000 (p < 0.05) for all variables, indicating significant differences before and after intervention. Conclusion: Leaflet-based education effectively improves knowledge, attitudes, practices, and PPE compliance among clinical dental students. This simple, reusable, and low-cost educational medium can be integrated into clinical orientation programs to strengthen infection prevention behaviors.